Pengaruh Suhu Ruangan Terhadap Distorsi Perubahan Dimensi Wax Selama 24 Jam - Kurniawan, Florencia Livia; Tjandrawinata, Rosalina; Pratiwi, Deviyanti; Margaretta, Dewi Liliany; Octarina, Octarina; Eddy, Eddy; Putri, Tansza Setiana (Ikatan Peminat Ilmu Material dan Alat Kedokteran Gigi (IPAMAGI), 2022)
Wax is a soft and flexible material obtained from plants and insects or made synthetically and composed of high molecular weight organic molecules. One of the properties of dental wax or wax is the property of distortion, namely the return of the modified form of dental wax or wax to its original shape. Wax patterns or wax models are used as wax patterns in the manufacture of orthodontic appliances, complete dentures, and other prostheses that use plastic construction. Base plate wax is a dental wax for denture patterns based on acrylic resin. To evaluate wax distortion that occurs at room temperature for 24 hours. Testing of 141 wax samples placed at room temperature 25°C for 24 hours. One-way ANOVA test revealed a significant difference (p<0.05) in storage of wax at room temperature for 24 hours. There is an effect of temperature and storage time on the amount of wax distortion that occurs.